Toward a Naturalized Aesthetics of Film Music: An Interdisciplinary Exploration of Intramusical and Extramusical Meaning. Issue 3 (1st December 2019) - Justus, Timothy
Abstract : In this article, I first address the question of how musical forms come to represent meaning—that is, the semantics of music—and illustrate an important conceptual distinction articulated by Leonard Meyer in Emotion and Meaning in Music between absolute or intramusical meaning and referential or extramusical meaning through a critical analysis of two recent films. Second, building examples of scholarship around a single piece of music frequently used in film—Samuel Barber's Adagio for Strings—I follow the example set by Murray Smith in Film, Art, and the Third Culture and discuss the complementary approaches of the humanities, the behavioral sciences, and the natural sciences to understanding music and its use in film.